Pathogenesis of the metabolic syndrome - Bergman, Richard (Henry Stewart Talks, 2007)
Metabolic syndrome and type 2 diabetes, Risk and effect of obesity, "Metabolic syndrome", Pathogenesis of the metabolic syndrome, Visceral and subcutaneous adiposity in the fat-fed dog model, "Overflow" hypothesis, Control diet and high fat diet, Visceral adiposity, Hepatic and peripheral insulin resistance, Distribution of insulin with obesity, Transendothelial insulin transport (TET), Hyperinsulinemia, Insulin resistance